MAJOR GENERAL SIR COLIN GUBBINS’ PRACTICAL HANDBOOK (Isagoge - Journal of Humanities and Social Sciences, 2023)
When the world prepared itself for what would be WWII, Colin Gubbins created a practical handbook in which he laid the foundations of guerrilla warfare as a methodology and an art largely contributing for the defeat of apparently stronger military forces employed by an attacking enemy on an apparently weaker force. Guerrilla, scientifically structured, is the equalizing tool that permits the initially weaker power to diminish the superiority of the stronger, thus allowing for a goal not just of a lighter defeat, but of a possible victory. This effectiveness of guerrilla warfare is most useful when the perspective of the attacked power is an existential one.